Augmented Reality in Thyroid Pathology Training: Evaluating Gamified Technology for Digital Educational Spaces - Kim, Se Jung; Yucel, Ibrahim; Grabski, Cynthia; Marollo, Kathleen (Encounters in Theory and History of Education / Rencontres en Théorie et Histoire de l'Éducation / Encuentros en Teoría e Historia de la Educación)

(untitled) (Faculty of Education, Queen's University, 2025)
The increasing accessibility of virtual reality (VR) and augmented reality (AR) technologies offers significant potential for high-fidelity educational simulations. However, current immersive learning tools often lack realistic haptic feedback, which is crucial for developing appreciative understanding in fields like nursing. When attempting gamification, there is a temptation to apply novel technology without deeply considering how the haptic and interactive design meets the learning goals of the instruction. This project addresses the gap in tactile simulation for nurse practitioner education, specifically focusing on thyroid and lymph node palpation. The proposed solution aims to enhance psychomotor skills, diagnostic reasoning, and self-efficacy by providing accessible, realistic tactile experiences outside traditional lab settings.